Evaluation of Tumor-Targeting Properties of an Antagonistic Bombesin Analogue RM26 Conjugated with a Non-Residualizing Radioiodine Label Comparison with a Radiometal-Labelled Counterpart - Maryam Oroujeni; Ayman Abouzayed; Fanny Lundmark; Bogdan Mitran; Anna Orlova; Vladimir Tolmachev; Ulrika Rosenström (MDPI AG, 2019)
Radiolabelled antagonistic bombesin analogues are successfully used for targeting of gastrin-releasing peptide receptors (GRPR) that are overexpressed in prostate cancer. Internalization of antagonistic bombesin analogues is slow. We hypothesized that the use of a non-residualizing radioiodine label might not affect the tumour uptake but would reduce the retention in normal organs, where radiopharmaceutical would be internalized. To test this hypothesis, tyrosine was conjugated via diethylene glycol linker to N-terminus of an antagonistic bombesin analogue RM26 to form Tyr-PEG2-RM26. [111In]In-DOTA-PEG2-RM26 was used as a control with a residualizing label. Tyr-PEG2-RM26 was labelled with 125I with 95% radiochemical purity and retained binding specificity to GRPR. The IC50 values for Tyr-PEG2-RM26 and DOTA-PEG2-RM26 were 1.7 ± 0.3 nM and 3.3 ± 0.5 nM, respectively. The cellular processing of [125I]I-Tyr-PEG2-RM26 by PC-3 cells showed unusually fast internalization. Biodistribution showed that uptake in pancreas and tumour was GRPR-specific for both radioconjugates. Blood clearance of [125I]I-Tyr-PEG2-RM26 was appreciably slower and activity accumulation in all organs was significantly higher than for [111In]In-DOTA-PEG2-RM26. Tumor uptake of [111In]In-DOTA-PEG2-RM26 was significantly higher than for [125I]I-Tyr-PEG2-RM26, resulting in higher tumour-to-organ ratio for [111In]In-DOTA-PEG2-RM26 at studied time points. Incorporation of amino acids with hydrophilic side-chains next to tyrosine might overcome the problems associated with the use of tyrosine as a prosthetic group for radioiodination.